1990
DOI: 10.1007/bf02247136
|View full text |Cite
|
Sign up to set email alerts
|

Lateral striatal cholinergic mechanisms involved in oral motor activities in the rat

Abstract: These experiments were undertaken to determine if local injection of pilocarpine in the neostriatum of the rat produces oral motor activities that are similar to those produced by systemic administration. In the first experiment, IP administration of 2.0-8.0 mg/kg pilocarpine increased chewing movements and tongue protrusions. In the second experiment, chronic guide cannulae were implanted bilaterally in ventromedial or ventrolateral striatum, and rats were injected with saline, 30, and 60 micrograms pilocarpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 33 publications
3
59
2
Order By: Relevance
“…VLS DA depletions have been shown to impair skilled use of the forepaws for functions such as reaching, grasping, feeding, food handling and lever pressing [19,20,39,65,66]. In addition, the VLS is an important region of the neostriatum for the control of oral motor activity [43,62,64,67]. It has been suggested that the lateral striatum of the rat is the homologue of the putamen of primates [67], and anatomical studies have demonstrated that the VLS of the rat receives input from headrelated areas of motor cortex [55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VLS DA depletions have been shown to impair skilled use of the forepaws for functions such as reaching, grasping, feeding, food handling and lever pressing [19,20,39,65,66]. In addition, the VLS is an important region of the neostriatum for the control of oral motor activity [43,62,64,67]. It has been suggested that the lateral striatum of the rat is the homologue of the putamen of primates [67], and anatomical studies have demonstrated that the VLS of the rat receives input from headrelated areas of motor cortex [55].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the lateral striatum of the rat is the homologue of the putamen of primates [67], and anatomical studies have demonstrated that the VLS of the rat receives input from headrelated areas of motor cortex [55]. Neurochemical mechanisms in the VLS involving several neurotransmitters, including DA, acetylcholine, and adenosine, have been implicated in tremulous jaw movements [21,26,39,54,64,67,74]. These movements, which are induced by DA antagonists, DA depletions, and cholinomimetics, have been used as a rodent model of parkinsonian tremor [14,37,67,69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis was performed using one-way ANOVA followed by Student-Newman-Keuls test. (* p < 0.05 was compared with the saline-treated wild type mice; # p < 0.05 was compared with the saline-treated µ-opioid receptor knockout mice) chewing movements (Kelley et al, 1989;Salamone et al, 1990). The nucleus accumbens of the ventral striatum is involved in motivational behavior such as reinforcement-related incentive learning (Robbins and Everitt, 1996;Kelley, 1999), while the nonlimbic dorsal striatum (caudate-putamen) is primarily involved in somatomotor functioning (Alexander and Crutcher, 1990;Graybiel et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic (Rupniak et al 1983(Rupniak et al , 1985Salamone et al 1990), g-aminobutyric acid (GABA)-ergic (Mithani et al 1987;Tamminga et al 1979;Lloyd et al 1985;Gunne et al 1988), and serotoninergic systems appeared to also be involved in the production of orofacial dyskinesia. Nevertheless, DA systems were still recognized as crucial in the development of TD.…”
Section: Evolution From Darss Hypothesis To Multineuronal Associationmentioning
confidence: 97%